Gear tooth profile optical reconstruction with rectified mounting error and vibration-induced measurement inaccuracies - Tian, Hao; Wu, Fan; Gong, Yongjun (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2025)
Accurate gear profile measurement is important for quality control and maintenance purposes in industrial production processes. In automated metrological systems, mechanical vibrations from drive train would introduce dynamic measurement uncertainties, in addition to the static installation error. To improve profiling accuracy, large and stationary devices may employ a bulkier setup for more dampened vibration amplitudes at higher excitation frequencies, but portable and hand-hold devices may not. In this paper, a method to rectify inherent structural-induced measurement error based on numerical optimization, and to reduce vibration-induced inaccuracies based on a segmented sinusoidal compensation function is proposed. An in-house built fully automatic noncontact gear measuring device using two opposing laser triangulation sensors is used to test the reconstructed tooth profile accuracy. Results show that the measurement error of the gear profile is reduced by 80% after compensating the mounting error, and by 30% after compensating the vibration error. The average gear measurement error after compensation is 0.0237 mm.